THE MODERATING ROLE OF LABOUR PRODUCTIVITY BETWEEN READYMADE GARMENT EXPORTS AND ECONOMIC GROWTH IN BANGLADESH - Khuky, Mahmuda Akter (The European Journal of Applied Economics, 2023)
This study investigates the moderating role of labour productivity on the relationship between readymade exports and economic growth in Bangladesh using annual time series data from 1983 to 2019 using the ARDL method. The most important factor that is impacting the competitiveness of Bangladesh’s Readymade Garment industry is poor labour productivity trends. A long-run positive relationship between RMG exports, labour productivity, and economic growth is observed. The RMG export earnings are significantly improving the economic growth of the country both in the long and short run. The policy implication is improving labour skills, providing training, and the use of information technology in the RMG sector will promote economic growth.